2013
DOI: 10.1097/pec.0b013e31828e56fb
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Cast Versus Splint for Distal Radial Buckle Fracture

Abstract: With the exception of pain reported in the emergency department being higher for the splinted group, all other measures, including convenience, satisfaction, and preference, showed a clear trend favoring splints at almost every time period in the study. This study provides additional evidence that splinting is preferable to casting for the treatment of distal radial buckle fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 12 publications
0
48
0
Order By: Relevance
“…Williams, et al (2013) concluded that there was significantly more 'resource utilisation' in cast group that in splint group. Resource utilisation compared in the study included assistant required when immobilisation was placed, time of immobilisation and physician delay of at least one hour from radiograph to immobilisation [28] . Although these might reflect cost, no cost figures were presented.…”
Section: Assessment Of Risk Of Bias In the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Williams, et al (2013) concluded that there was significantly more 'resource utilisation' in cast group that in splint group. Resource utilisation compared in the study included assistant required when immobilisation was placed, time of immobilisation and physician delay of at least one hour from radiograph to immobilisation [28] . Although these might reflect cost, no cost figures were presented.…”
Section: Assessment Of Risk Of Bias In the Included Studiesmentioning
confidence: 99%
“…Davidson, et al (2001) and Karimi, et al (2013) recruited subjects in orthopaedic fracture clinic after they received different intervention when diagnosed in emergency department [6,29] . The other two studies [7,28] can be included with caution and discussion on the risk of bias in both of the two trials.…”
Section: Literature Search and Selection Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations